Discretion as a policy tool - an analysis of the National Bank of Poland's role in intervention strategies during the economic crisis - Konrad Trzonkowski (Journal of Modern Science, 2025)
Objectives The decision-making discretion of the National Bank of Poland (NBP) plays a key role in enhancing the country's economic stability during economic crises. The premise is that flexibility and the ability to respond quickly to changing economic conditions are essential for effective economic management in times of crisis. Decision-making discretion allows the National Bank of Poland to take non-standard actions that would not be possible under a rigid policy based on predetermined rules.